Oxford Handbooks Online 2014
DOI: 10.1093/oxfordhb/9780199795574.013.13
|View full text |Cite
|
Sign up to set email alerts
|

How Gender Shapes Emerging Adulthood

Abstract: This chapter examines how gender shapes experiences in emerging adulthood, from identity development and relationships to involvement in risky behaviors and mental health outcomes. It first considers the developmental tasks commonly faced by emerging adults before proceeding to a discussion of gender differences between young men and women in terms of development of one’s identity and relationships with family members (parents and siblings), friendships, and romantic relationships and sexual experiences, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Gender is recognized as an important social determinant of health [ 41 , 42 , 43 ], and although gender differences have been found in all study variables, except the number of life events experienced during the last year, the most important predictors of emerging adult men and women’s psychological distress were the same variables. The exception was the detachment coping style that was negatively associated with psychological distress only in the male group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender is recognized as an important social determinant of health [ 41 , 42 , 43 ], and although gender differences have been found in all study variables, except the number of life events experienced during the last year, the most important predictors of emerging adult men and women’s psychological distress were the same variables. The exception was the detachment coping style that was negatively associated with psychological distress only in the male group.…”
Section: Discussionmentioning
confidence: 99%
“…Gender refers to socially constructed norms, behaviors, activities, relationships and attributes that society considers appropriate for women and men [ 40 ], and it is recognized as an important social determinant of health [ 40 , 41 , 42 ]. Given that emerging adulthood is characterized by identity issues in identifying oneself and what one wants to be, and it requires young men and women to explore their future possibilities, gender can play a crucial role in the ongoing development of one’s identity, as well as in relationships with romantic partners, friends and family, and in the implications of risk behaviors and in associated mental health outcomes [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, emerging adults are more independent from their parents than in previous years because they are able to make their own decisions and plan their own futures (Norona, Preddy, & Welsh, ). Some researchers have found that emerging adults’ parents foster their autonomy to a moderate or large extent during their transition to adulthood (Inguglia, Ingoglia, Liga, Lo Coco, & Lo Cricchio, ).…”
Section: The Family System During Emerging Adulthoodmentioning
confidence: 99%
“…Some researchers have found that emerging adults’ parents foster their autonomy to a moderate or large extent during their transition to adulthood (Inguglia, Ingoglia, Liga, Lo Coco, & Lo Cricchio, ). However, parents also provide them with financial support, meaning that they remain economically dependent (Fingerman & Yahirun, ; Norona et al., ). Specifically, 84.7% of young Spaniards claim that they need to resort to another source of income besides their own (mainly their parents), in order to make ends meet (INJUVE, ).…”
Section: The Family System During Emerging Adulthoodmentioning
confidence: 99%
“…As mentioned above, the existence of emerging adulthood as a period is prompted by a delay in the acquisition of adult roles, which entails changes in family dynamics (Kins, Beyers & Soenens, ). Specifically, and in contrast to past decades, many young adults now stay in their family home and remain economically dependent on their parents (Fingerman & Yahirun, ; Norona, Preddy & Welsh, ). In this new context, parent‐child relationships must find a new balance based on more egalitarian and symmetrical relationships between parents and their offspring (Kins, Soenens & Beyers, ; Koepke & Denissen, ; Manzi, Regalia, Pelucchi & Fincham, ; Parra, Oliva & Reina, ).…”
Section: Introductionmentioning
confidence: 99%